Virginia Guzmán Quesada, Rafael Martínez Somarribas, Miguel Montero, Leticia Cubero. - Universidad Estatal a Distancia (San José, Costa Rica : UNED, 2025)
Grupo pequeño de personas
Colección Fototeca UNED
Keywords: Guzmán Quesada, Virginia; Martínez Somarribas, Rafael; Montero, Miguel; Cubero, Leticia; FOTOGRAFÍAS; UNIVERSIDAD ESTATAL A DISTANCIA -- COSTA RICA; FOTOTECA